Adam Smith on uncertainty and security (Part 2) - Bekryashev, Andrey (Теоретическая и прикладная экономика, 2025)
The subject of the research in the second part of the article is Adam Smith's conceptual ideas on uncertainty. The study was undertaken to identify and systematize the elements of the concept of uncertainty in the works of Adam Smith, showing their connection with the philosophy of David Hume and modern economic theories. The connection of Smith's ideas with Hume's probability theory is analyzed and an alternative to interpretations that assume the similarity of the positions of Smith and Keynes is proposed. It is shown that Smith developed a classification of uncertainty levels that has points of intersection with modern institutional theory (D. North). It is substantiated that Smith considers heuristics as a tool for reducing uncertainty, which brings his ideas closer to modern behavioral economics (G. Gigerenzer). Interpretations that emphasize the role of interval probability in his works (M.E. Brady) are questioned. The study demonstrates that Smith's concept, based on Hume's philosophy, contains elements that anticipate modern decision-making theories. The research methodology is based on a combination of antiquarian and presentist approaches. The following were used: textual analysis of the works of Smith and Hume, comparative historical method, conceptual reconstruction and critical analysis of interpretations. Interdisciplinary synthesis allowed us to link classical ideas with modern economic theories. The study offers a new interpretation of the concept of uncertainty in the works of Adam Smith, making four significant contributions to the history of economic thought. First, a systematic analysis of the connection of his ideas with Hume's probability theory was carried out, which made it possible to offer an alternative to common interpretations that emphasize the similarity of the views of Smith and Keynes (M.E. Brady). Secondly, an original classification of Smith's levels of uncertainty by ways of reducing it (information, knowledge, institutions, irrational means) was revealed, anticipating modern institutional approaches. Thirdly, the interpretation of Smith's "hard rules" as a prototype of modern heuristics for reducing uncertainty (G. Gigerenzer) in behavioral economics is substantiated. Fourthly, the corpus of analyzed texts is expanded by little-studied works of Smith (Lectures on Jurisprudence, History of Astronomy) in relation to the problem of uncertainty. The obtained results revise the Keynesian interpretations of Smith's ideas on uncertainty proposed in the literature, identify new historical parallels with the theory of bounded rationality, linking classical political economy with modern economic and philosophical discussions.